Chemistry and pharmacological diversity of quinoxaline motifs as anticancer agents - Ajani Olayinka O.; Nlebemuo Martins T.; Adekoya Joseph A.; Ogunniran Kehinde O.; Siyanbola Tolutope O.; Ajanaku Christiana O. (Acta Pharmaceutica)
Surpassing heart diseases, cancer is taking the lead as the deadliest disease because of its fast rate of spreading in all parts of the world. Tireless commitment to searching for novel therapeutic medicines is a worthwhile adventure in synthetic chemistry because of the drug resistance predicament and regular outbreak of new diseases due to abnormal cell growth and proliferation. Medicinal chemistry researchers and pharmacists have unveiled quinoxaline templates as precursors of importance and valuable intermediates in drug discovery because they have been established to possess diverse pharmacological potentials. Hence, this review highlights the current versatile routes to accessing functionalized quinoxaline motifs and harnessing their documented therapeutic potentials for anticancer drug development.